Utility of ADC measurement on diffusion-weighted MRI in differentiation of prostate cancer, normal prostate and prostatitis - Esen, Meltem; Onur, Mehmet Ruhi; Akpolat, Nusret; Orhan, Irfan; Kocakoc, Ercan (Ame Publishing Company, 2013)
To determine the utility of apparent diffusion coefficient (ADC) values in differentiation of prostate cancer from normal prostate parenchyma and prostatitis we obtained ADC values of 50 patients at b 100, 600 and 1,000 s/mm(2) diffusion gradients. The ADC values of prostate cancer group were significantly lower than normal prostate and prostatitis group at b 600 and 1,000 s/mm(2) gradients. The ADC values at high diffusion gradients may be used in differentiation prostate cancer from normal prostate and prostatitis.
Keywords: Diffusion-weighted MR imaging; prostate cancer; apparent diffusion coefficient (ADC); prostatitis